2016
DOI: 10.22494/cot.v4i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune response in rats with 1,2-dimethylhydrazine-induced colon cancer after transplantation of placenta-derived multipotent cells

Abstract: We describe the state of the immune system at the late stage of 1,2-dimethylhydrazine (DMH)-induced colon cancer and after administration of placenta-derived multipotent cells (PDMCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…These data are consistent with the results of research by Caprezo N. O. et al [12], observed the appearance of dystrophic zones in the spleen and damage to the nuclear apparatus of its cells when exposed to N,N-dimethylhydrazine hydrochloride. Research by Svitina H. M. et al [25] demonstrated a decrease in the proliferative activity of splenocytes under the influence of N,N-dimethylhydrazine hydrochloride. According to the analysis conducted by Li B. et al [17], the spleen plays a dual role in cancer incidence and progression.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the results of research by Caprezo N. O. et al [12], observed the appearance of dystrophic zones in the spleen and damage to the nuclear apparatus of its cells when exposed to N,N-dimethylhydrazine hydrochloride. Research by Svitina H. M. et al [25] demonstrated a decrease in the proliferative activity of splenocytes under the influence of N,N-dimethylhydrazine hydrochloride. According to the analysis conducted by Li B. et al [17], the spleen plays a dual role in cancer incidence and progression.…”
Section: Discussionmentioning
confidence: 99%